Poppy Harmon investigates [large type] - Hollis, Lee (Hollis, Lee. Desert Flowers mysteries., 2018)
Unexpectedly finding herself a penniless widow with no real skills, Poppy Harmon opens the Desert Flowers Detective Agency with her two best friends, Violet and Iris, and takes on a burglary investigation that quickly becomes a dangerous case of murder.